Petunjuk praktis mengatasi gangguan kesehatan di rumah anda Keith W. Sehnert, Howard Eisenberg ; alih bahasa, Indriani K. Sumadikarya - SEHNERT, Keith .W; EISENBERG, Howard; SUMADIKARYA, Indriani K (1980)
298 hlm ilus 21 cm